2015
DOI: 10.1039/c4ra13026j
|View full text |Cite
|
Sign up to set email alerts
|

Superior CO2 adsorption from waste coffee ground derived carbons

Abstract: Utilising the hugely abundant waste from spent coffee grounds (CGs), KOH activated highly microporous carbons with surface areas of 2785 m 2 g À1 and micropore volumes of 0.793 cm 3 g À1 were synthesised that are capable of uptake capacities near 3 mmol g À1 at 50 C and 1 bar. Importantly such uptake capacities are achieved though the material's superior microporous character and without doping within the carbon matrix, thereby ensuring facile regeneration with a binding enthalpy of only 26 kJ mol À1 and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 44 publications
0
32
1
Order By: Relevance
“…For instance, the sample that exhibits predominant porosity of around 0.7 nm along with a much smaller proportion of pores of size below 1.5 nm and SSA BET of 1551 m 2 g −1 has shown CO 2 uptake of 7.4 mmol g −1 . Microporous carbons derived from coffee‐waste show CO 2 capacity of 7.5 and 7.2 mmol g −1 for SSA BET of 1620 and 2070 m 2 g −1 , respectively, with more than 90% of the porosity in the <1.5 nm region . UMCs also exhibit a clear porosity‐dependent uptake trend, where a linear correlation can be established between uptakes and SSA BET or micropore volume (Figure c,g).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…For instance, the sample that exhibits predominant porosity of around 0.7 nm along with a much smaller proportion of pores of size below 1.5 nm and SSA BET of 1551 m 2 g −1 has shown CO 2 uptake of 7.4 mmol g −1 . Microporous carbons derived from coffee‐waste show CO 2 capacity of 7.5 and 7.2 mmol g −1 for SSA BET of 1620 and 2070 m 2 g −1 , respectively, with more than 90% of the porosity in the <1.5 nm region . UMCs also exhibit a clear porosity‐dependent uptake trend, where a linear correlation can be established between uptakes and SSA BET or micropore volume (Figure c,g).…”
Section: Resultsmentioning
confidence: 57%
“…Specifically, at a low CO 2 partial pressure of 0.15 bar, as a standard concentration in the postcombustion flue‐gas, the samples with ultranarrow pores show high CO 2 capture capacity, reaching to 2.75 mmol g −1 (≈12.1 wt%). The maximum capacity of 7.9 mmol g −1 (≈34.6 wt%) at 1 bar is also one of the highest values reported so far in the wide range of porous solids, including N‐doped activated carbons (ACs), MOFs (of open‐metal centers, micropores and flexible frameworks), microporous polymers, and solid‐amines . Uptake values deduced at 273 K and 1 bar in such different categories of materials family with respect to their SSA BET are comparatively summarized in Figure g.…”
Section: Resultsmentioning
confidence: 88%
“…Theadsorption isotherms showed that the pores in starch-derived Starbons were disordered slit-shaped (H3type isotherm according to IUPAC classification), whilst those in alginic acid-based Starbons were interconnected ink-bottle shaped (H2-type isotherm). [11] It is apparent from Figure 1t hat some of the Starbon samples could outperform the CO 2 adsorption capacity of AC by up to 50 %(and by up to 65 %at10bar CO 2 pressure). Themass difference between the end of the pressurization and vacuum steps was used to calculate the number of mmols of CO 2 adsorbed per gram of sample.…”
mentioning
confidence: 92%
“…Referring to the recent work published on chemically activated carbon, it is shown that this yield is more important that KOH activation of biomass. Travis et al [23] have synthesized a series of KOH activated carbons from spent coffee grounds. Sample yields ranged from 11 to 16 wt % with yields lower for higher KOH.…”
Section: Chemical Activationmentioning
confidence: 99%